2022
DOI: 10.3389/fgene.2022.911119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ferroptosis-Related Molecular Clusters and Immune Characterization in Autism Spectrum Disorder

Abstract: Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with clinical presentation and prognostic heterogeneity. Ferroptosis is a regulated non-apoptotic cell death program implicated in the occurrence and progression of various diseases. Therefore, we aimed to explore ferroptosis-related molecular subtypes in ASD and further illustrate the potential mechanism.Methods: A total of 201 normal samples and 293 ASD samples were obtained from the Gene Expression Omnibus (GEO) database. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, there are few studies on the role of ferroptosis in the pathophysiology of ASD. Only one clinical study indicated that higher levels of ferroptosis scores were associated with immune activation in 293 ASD patients [52]. DHA plays an important role in lipid mediator production [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies on the role of ferroptosis in the pathophysiology of ASD. Only one clinical study indicated that higher levels of ferroptosis scores were associated with immune activation in 293 ASD patients [52]. DHA plays an important role in lipid mediator production [53].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the methods of previous studies, hub genes for depression diagnosis were selected (14,15). Four machine learning methods, including least absolute shrinkage and selection operator (LASSO) regression, random forest model (RF), support vector machine model (SVM), generalized linear model (GLM) were performed to evaluate the value of S-DEGs in diagnosing depression.…”
Section: Construction and Evaluation Of Diagnostic Model And Molecula...mentioning
confidence: 99%